Rubrikasi dalam Naskah Sěrat Rama (PB A.243/L291) Koleksi Perpustakaan Museum Sonobudoyo Yogyakarta - Tio Cahya Sadewa (Jumantara: Jurnal Manuskrip Nusantara, 2019)
The manuscript in this research is Sěrat Rama, collection of the Yogyakarta Sonobudoyo Museum Library with the collection code PB A.243 / L291. In the colophon, it was stated that the initiator was B.P.H Jayakusuma, the son of the Sultan Sepuh (HB II). Pages 1—11 were copied on Wednesday Wage, 1 Sura, Alip 1835 (March 8, 1905) whereas page 12 onwards written in older model, estimated to be copied around the middle to late 19th century. What's interesting about this manuscript is the presence of the rubric inside. The rubric contained in Sěrat Rama manuscript is a type of decorative rubric. There is a form of rubric accompanied by writing and there is also a rubric which is only a picture of flowers. Based on the location, rubrication divided into two, there are in the margins of the manuscript pages and between the text. Each type of rubrication also has its own function and meaning. Therefore, this study aims to describe the types, functions, and meanings of the rubrics contained in the Sěrat Rama script. To analyze the meaning, Charles Sanders Pierce's semiotic approach is used. Thedescriptive analytic is used as the research method. The expected results of this study are in the form of a description of the types of rubrication, function, and their meaning. Knowing the meaning of the rubric contained in Sěrat Rama's text will make it easier to understand the contents of the story.